Analysis of Reforms In Qarshi City In The Late 13th To Early 14th Centuries - Hikmatullayevich, Nasrullayev (Buletin Antropologi Indonesia, 2025)
The article discusses the fact the cities of Mavaraunnahr in the late 13th to early 14th centuries were characterized by relentless power struggles among Mongol khans, descendants of Chingiz. This period's socio-cultural condition was marked by the division of the region into small, powerless states and the aspiration of each ruler to subjugate the entire Mavaraunnahr under a single authority. It is analyzed that Kebek Khan (718/1318-726/1326), a skilled politician and adept reformer, played a significant role during this time. He built the city of Qarshi, which later became a major center of the region. Kebek Khan's monetary and administrative reforms had a positive impact on the socio-political life of Mavaraunnahr. Despite the challenges, including invasions and internal power struggles, cities like Qarshi and Nasaf witnessed significant economic, political, and cultural growth. The flourishing of construction, culture, and science, particularly during the reign of Amir Timur and his successors is also described.